STRYV365 peak team and Brain agents: teacher perspectives on school impact of a trauma-informed, social–emotional learning approach for students facing adverse childhood experiences - Stoltenburg, Abbey; McGuire, Madison; Liverman, Elizabeth; Lumelsky, Paula; Bates, Garrett; Gundacker, Constance; Currie, Brandon; Meurer, John R. (Frontiers in Psychology, 2024)
Introduction Adverse childhood experiences (ACEs) have a profound impact on children’s and adolescents’ academic performance and overall wellbeing. In contrast, positive childhood experiences help mitigate the negative effects of ACEs on health and wellbeing. Trauma-informed and social–emotional learning (SEL) programs in schools may address these impacts, with school staff playing a pivotal role in ensuring their success and influencing school outcomes. This study aimed to assess the strengths, weaknesses, and areas for improvement in the STRYV365 peak team and Brain Agents programs. The aim was to refine program implementation and determine the preliminary effects on students, teachers, and the broader school environment. Methods To achieve this goal, four focus groups were conducted after the program concluded, involving 17 school leaders, administrators, and teachers from four urban schools serving students in fifth through ninth grades. The audio transcripts were professionally transcribed and analyzed by four co-authors using Dedoose for inductive coding, leading to the identification of major themes and subthemes. Results Three key themes were identified from transcripts: school-wide perspectives of STRYV365 programs, strengths and impacts of STRVY365 programs, and suggestions for program improvement. School staff noted that the peak team was particularly engaging for students, helping them develop SEL skills and foster both peer-to-coach and peer-to-peer relationships. Additionally, the STRYV365 programs were found to enhance student–teacher relationships and staff relationships. Teachers expressed strong interest in taking a more active role in future programming. Discussion Overall, this study highlights the importance of teacher and administrator involvement in maintaining consistent SEL activities for urban youth. The findings also suggest that short-term, 4-week SEL programs can have a positive effect on school culture, as well as on student–teacher relationships and teacher–teacher relationships.